Writing Errors: The Case of English Learners of Arabic - Asmaa Shehata; Amaya Martin (Journal of Linguistics and Language Teaching)
Errors made by second language (L2) learners are problematic and frustrating to both learners and teachers. This study aimed to find areas of difficulty in writing among learners of Arabic. It examined the types of errors that learners of Arabic who were first language (L1) English speakers made in writing and investigated the influence of language proficiency on learners’ writing errors. To this end, 30 essays were collected from learners of Arabic at three different class levels: beginner, intermediate and advanced. The findings indicated that learners made more grammatical than lexical and spelling errors. While definiteness was the most frequent error made by first- and second-year learners, noun-adjective agreement was the most common type of grammatical error made by third-year learners. The results hold implications for the type of input introduced to L2 learners to improve their language learning.